2019
DOI: 10.14740/gr1132
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Quick Sepsis-Related Organ Failure Assessment Scores in Patients With Acute Pancreatitis Who Present to Emergency Departments: A Three-Year Cohort Study

Abstract: Background Distinguishing sepsis from other inflammatory syndromes continues to be a clinical challenge. The goal of risk stratification tools is to differentiate sepsis from other conditions. We compare the ability of quick sepsis-related organ failure assessment (qSOFA) and systemic inflammatory responses syndrome (SIRS) scores to predict prolonged length of stay (LOS) among patients who presented to the emergency department and hospital ward with acute pancreatitis (AP). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…22) Furthermore, the activation of TLR4 expressed in pancreatic acinar cells can promote the secretion of IL-1β, which further alters intestinal permeability and causes other manifestations of pancreatitis. 23) Previous study has also shown that activation of inflammatory responses and bacterial translocation after intestinal injury are major risk factors for AP. 24,25) In this context, we considered that intervening in the pathogenesis of AP would be an effective way to treat it.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…22) Furthermore, the activation of TLR4 expressed in pancreatic acinar cells can promote the secretion of IL-1β, which further alters intestinal permeability and causes other manifestations of pancreatitis. 23) Previous study has also shown that activation of inflammatory responses and bacterial translocation after intestinal injury are major risk factors for AP. 24,25) In this context, we considered that intervening in the pathogenesis of AP would be an effective way to treat it.…”
Section: Discussionmentioning
confidence: 98%
“…23) Previous study has also shown that activation of inflammatory responses and bacterial translocation after intestinal injury are major risk factors for AP. 24,25) In this context, we considered that intervening in the pathogenesis of AP would be an effective way to treat it. EDA has a significant beneficial effect in liver injury 26) and in cerebral ischemia.…”
Section: Discussionmentioning
confidence: 98%
“…Further, selection bias may exist, as patients who were discharged directly from the ED were excluded from the analysis; this limits the analysis to those with more severe cases of acute pancreatitis. We did not perform a direct comparison between the ED-SAS score and other common scoring systems or ED predictors of mortality such as the quick Sepsis Related Organ Failure Assessment score, which may have utility in evaluating acute pancreatitis, as it does in sepsis [ 26 ]. In addition, the design for assessing mortality may underestimate the true rates, given that subjects were not directly contacted, as electronic health record data were used to determine 30- and 180-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The qSOFA score has been used as a new tool for sepsis and septic shock [ 4 ]. It was developed as a risk stratification tool for patients who are admitted outside the ICU, such as those in ED [ 11 13 ]. Seymour et al [ 11 ] studied 148,907 suspected infected patients, of whom 4% died.…”
Section: Discussionmentioning
confidence: 99%